Assessment of oral health of the Serbian Armed Forces members - Lekić, Margareta; Lazić, Zoran; Pandjaitan Donfrid, Paulina; Bokonjić, Dubravko; Lemić, Tatjana; Daković, Dragana (Vojnosanitetski pregled, 2021)
Background/Aim. Oral health is an integral part of general health. The state of oral health greatly affects the psychological and physical condition of patients. The aim of study was to determine oral health among the Serbian Armed Forces members. Methods. This prospective cross-sectional pilot study was conducted on 648 examinees at the mean age of 34.47 ± 8.14 years who had dental check-ups. All the categories of military personnel aged 18–64 years were divided into five groups. Assessment of oral health was obtained by clinical examination and the personal perception of oral health obtained by fulfilling the questionnaire “Oral Health Questionnaire for Adults” of the World Health Organization. The results obtained by processing questions from the questionnaire were compared with the data of clinical examination. Results. The average value of the the Decayed, Missing and Filled Teeth (DMFT) index was 10.55 ± 4.79; the mean value of decayed teeth per participant was 2.00 ± 2.55, and on average, each respondent was missing 3.21 ± 3.35 teeth. Based on data obtained from the questionnaire, 39.4% of the participants smoked cigarettes. The majority of subjects (58.3%) brushed their teeth regularly two or more times a day. Oral health as poor was assessed by 18.9% of the participants. Participants who brush their teeth less than twice a day evaluated their oral health as poor 3.08 times more often compared to those who brush their teeth more than twice a day. Conclusion. The self-assessment of poor oral health significantly failed when compared with a high value of DMFT which means that only a small percentage of participants evaluated their oral health objectively.